2021
DOI: 10.1093/jeea/jvab041
|View full text |Cite
|
Sign up to set email alerts
|

Do Research Joint Ventures Serve a Collusive Function?

Abstract: Every year thousands of firms are engaged in research joint ventures (RJV), where all knowledge gained through R&D is shared among members. Most of the empirical literature assumes members are non-cooperative in the product market. But many RJV members are rivals leaving open the possibility that firms may form RJVs to facilitate product market collusion. We examine this by exploiting variation in RJV formation generated by a policy change that affects the collusive benefits but not the research synergies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Further, she concludes that firms are more likely to join an RJV the more they spend on R&D. Link (1998) provides case-study evidence for efficiencies in a specific RJV. Finally, Duso et al (2014) and Sovinsky (2022) find empirical evidence that RJVs among competitors are more prone to collusion, which reduces welfare. Thus, horizontal R&D cooperation should come under scrutiny by authorities.…”
Section: Relation To the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Further, she concludes that firms are more likely to join an RJV the more they spend on R&D. Link (1998) provides case-study evidence for efficiencies in a specific RJV. Finally, Duso et al (2014) and Sovinsky (2022) find empirical evidence that RJVs among competitors are more prone to collusion, which reduces welfare. Thus, horizontal R&D cooperation should come under scrutiny by authorities.…”
Section: Relation To the Literaturementioning
confidence: 99%
“…22 Note, however the empirical work suggesting that RJVs may foster collusion (Duso, Röller, and Seldeslachts (2014) and Sovinsky (2022)).…”
Section: Mergers Vs Rjvsmentioning
confidence: 99%
“…Harrington and Chang (2015) extend this model by introducing leniency together with capacity constraints for the CA and endogenize the intensity of non-leniency enforcement (Motta and Polo (2003) and Spagnolo (2008)). Duso et al (2014), Heim et al (2022) and Sovinsky (2022) use the introduction of leniency programs as exogenous shocks to test whether horizontal cooperation (joint ventures and controlling shareholders, respectively) declines. In contrast, Miller (2009) shows increased cartel detection after the introduction of the leniency program in 1993, but no sign for an increase in deterrence in a sample of convicted cartels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that network investment related communication facilitated a collusion at retail level, but did not lead to more investment. Sovinsky and Helland [2018] provided empirical evidence that R&D joint ventures can serve a collusive function. They showed that the revision of antitrust rules in the 1990s in the US to decrease collusive agreements, was followed by a significantly reduced joining, therefore it highlights that coordination in R&D dimension may facilitate coordination in other dimensions.…”
Section: Anticompetitive Effects (Drawbacks)mentioning
confidence: 99%